Justicia carajensis, a new species of Acanthaceae from the Serra dos Carajás, Pará, Brazil - Silva, Fabio Araújo Da; Gil, André Dos Santos Bragança; Kameyama, Cíntia (Phytotaxa, 2019)
A new species, Justicia carajensis, is described from the Serra dos Carajás as part of the ongoing taxonomic study of Justicia from the state of Pará in northern Brazil. Morphologically, it belongs to Justicia sect. Chaetothylax, and differs from other species by a combination of characters of calyx lobe length and indumentum, corolla tube shape, anther morphology, and ovary and fruit indumentum.